Improving Student's Vocabulary Skill Through Englishvit Program On Tik-Tok At Mts Al – Hidayah Bekasi - Utomo, Agung Diva; Hidayati , Dini; Edi, Syamsi (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this study is to improve students' vocabulary mastery and their learning activities by using the TikTok application to improve students' vocabulary mastery at MTS Al Hidayah Bekasi. This research uses action research method. Based on research conducted through the Class Action Research (CAR) method, the researcher concluded that the use of the Tik-Tok Application is a very influential learning medium in helping to improve the mastery and skills of English vocabulary in grade 8 MTS Al Hidayah Bekasi.